Escritas de si e fabulação da memória no cinema autobiográfico de Alejandro Jodorowsky - Lima Filho, Agamenon Porfírio de (2020)
Along his cineautobiographies The dance of reality (2013) and Endless Poetry (2016), diretor Alejandro Jodorowsky recalls and reimagines his past. We analyze these products in order to understand how memories are addressed, represented and re-elaborated by Jodorowsky and what these processes demonstrate on the possibilities of autobiographical cinema. Thus, we structure our investigation in four axes: the study of autobiographies, self-narratives, memory and cinema. Due to the hybridness of the subject, we turn to theorists such as Philippe Lejeune (2014) and George Gusdorf (1991) to discuss autobiography and the writing on the Self; Henri Bergson (1999) e Maurice Halbwachs (1990) to discuss memory; Jöel Candau (2018) e Paul J. Eakin (2019) on the intercrossing between memory and self-narratives in identity building; and David Bordwell (2008), Jacques Aumont e Michel Marie (2019) on film theory. Therefore, we seek to identify the ways in which Jodorowsky structures his self-narratives and puts his memories into play.